Urgensi Ilmu Fiqh al-Hadits dalam Memahami Hadis Nabi Muhammad - Rauf, Rusmin Abdul (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This article provides a concise overview of the significance, principles, benefits, as well as the renowned Companions and their disciples who played pivotal roles in shaping major fiqh schools across various regions. The study of Fiqh al-Hadith holds immense importance in the Islamic community and among researchers. It involves a deep understanding of the Prophet's Sunnah, the chains of transmission, the content of hadiths, and the legal principles within. The significance of Fiqh al-Hadith is undeniable; it stands as the second source of Islamic law after the Quran. Accurate comprehension is essential for precise legal decisions and aligning with Islamic principles, adapting them to evolving societal changes and technological advancements. This research found that Fiqh al-Hadith's paramount importance, considering historical context and the Arabic language barrier. Misinterpretations can lead to deviations and distortions of religious teachings. Neglecting the principles of understanding hadiths can result in extremism and manipulation. Hence, comprehensive and accurate comprehension is vital. Furthermore, Fiqh al-Hadith is esteemed by prominent scholars. It is regarded as half of knowledge, acknowledged by Imam Ali bin al-Madini and Imam al-Bukhari. In the modern era, the study of Fiqh al-Hadith evolves and adapts to technological advancements and the evolving needs of the Muslim community.